Seeding performance of air-assisted centralized seed-metering device for rapeseed - Lei, Xiaolong; Hu, Hongji; Yang, Wenhao; Liu, Liyang; Liao, Qingxi; Ren, Wanjun (International Journal of Agricultural and Biological Engineering, 2021)
In order to analyze seed movement characteristics and improve seeding quality of air-assisted centralized metering device for rapeseed, the effects of the model-hole structure on seed feeding performance were investigated using EDEM simulation. Furthermore, the CFD-DEM coupling approach was applied to determine movement trajectories and airflow fields. The impacts of rapeseed varieties and rotational speed on seeding performance were investigated by bench tests. The results showed that the seed feeding quantity increased with the increase of model-hole’s length, depth and section size. Under the model-hole’s depth of 3.0 mm, the type Ⅱ model-hole and model-hole’s length of 10 mm, both the variation coefficient of seed feeding quantity and hill diameter were lower which meet the seeding quantity requirement of 2 seeds in each hill. It was revealed that the seed population migrated in a large airflow velocity area and the distribution was uniform. The bench tests indicated that rapeseed varieties and rotational speed had a significant effect on the seed feeding quantity in each hill at rotational speed of 10-40 r/min. The variation coefficient of seed feeding quantity in each hill was less than 17.0% for each treatment. The hill diameter, which did not exceed 3.5 cm, tended to reduce with increasing rotational speed. The variation coefficient of seeding quantity in each row and seeding uniformity was less than 6.5% and 32.0%, respectively. Field experiments demonstrated that the seedling was 9-13 plants per meter each row for three rapeseed varieties. The variation coefficient of plants was less than 25.0% for six rows and their yields reached 2761 kg/hm2, which realized the mechanized planting requirements. The results can optimize structure of an air-assisted centralized metering system and improve in seeding performance.Keywords: rapeseed, air-assisted centralized metering device, seed hill feeding, seeding performanceDOI: 10.25165/j.ijabe.20211405.5349Citation: Lei X L, Hu H J, Yang W H, Liu L Y, Liao Q X, Ren W J. Seeding performance of air-assisted centralized seed-metering device for rapeseed. Int J Agric & Biol Eng, 2021; 14(5): 79–87.